A Comprehensive Study of the Need for Emotional Health and Mental Health Support Programs in Educational Institutions - Ray, Debmalya (Journal of Educational Research and Policies, 2025)
The mental health of students and teachers is a critical concern that significantly impacts their overall well - being, academic performance, and ability to function effectively within educational settings. This study aims to comprehensively assess the mental health status of students and teachers in an educational institution by employing two well - established instruments: the Mental Health Questionnaire and Beck's Depression Inventory (BDI). The study involved a total of 439 participants, comprising 186 students and 253 teachers, providing a broad perspective on the mental health challenges within the institution. The Mental Health Questionnaire was designed to gather insights into the multifaceted challenges faced by participants in their lives, academic pursuits, and relationships both within and outside the institution. The BDI, developed by Aaron T. Beck in the 1960s, is a widely used instrument for measuring the presence and severity of depressive symptoms through 21 multiple - choice questions. Key findings from the study indicate alarmingly high levels of emotional distress among students, with 61.7% experiencing severe to crisis - level emotional distress, significantly higher than the global average of 30.19%. Moreover, 28.3% of students expressed suicidal intentions, which is notably higher than the global average of 16.9%. Additionally, 65.7% of students reported severe to crisis - level emotional turmoil, and 46.9% experienced a severe to crisis - level complete loss of motivation. Issues related to the mind - body connection were reported by 57.8% of students, while 33.3% felt lonely, which aligns with the global average of 33%. Anger issues were noted by 17.1% of students, and 9.6% faced challenges related to friendships. The need for mental health support was overwhelmingly evident, with 99.4% of students expressing the need for a dedicated mental health program. Furthermore, 45.5% of students indicated a need for personal guidance and mentorship, 79.1% believed counseling for parents is required, and 90.1% thought counseling for teachers is necessary. The BDI analysis revealed that 39.24% of students fall within the minimal to no depression range, 16.46% in the mild depression range, 20.25% in the moderate depression range, and 21.51% in the severe depression range. This distribution highlights that over half (53.22%) of the student population is experiencing some level of depression, necessitating urgent and proactive mental health interventions. The study underscores the importance of implementing comprehensive mental health programs within educational institutions to address the high prevalence of emotional distress and depressive symptoms. Proactive mental health interventions are essential to fostering a supportive learning environment, ensuring that students and teachers can achieve their full potential both academically and personally.